2020
DOI: 10.1002/ajh.25992
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient evidence exists to use histopathologic subtype to guide treatment of idiopathic multicentric Castleman disease

Abstract: Frits van Rhee 22 | the Castleman Disease Collaborative Network Scientific Advisory Board diagnostic criteria international working group and treatment guidelines international working group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…18,19 We previously reported that patients with both iMCD and TAFRO had uniform clinical features and pathological findings with hyper-vascular proliferation in lymph nodes as well as myelofibrosis and megakaryocyte hyperplasia in bone marrow. 13,20 Thereafter, iMCD patients with TAFRO (iMCD-TAFRO) symptoms have been considered to have an aggressive clinical subtype of iMCD. 19 The iMCD patients who do not meet the criteria for TAFRO often have elevated platelet counts, hypergammaglobulinemia, and a less aggressive course; these cases are described as iMCD not otherwise specified (iMCD-NOS).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 We previously reported that patients with both iMCD and TAFRO had uniform clinical features and pathological findings with hyper-vascular proliferation in lymph nodes as well as myelofibrosis and megakaryocyte hyperplasia in bone marrow. 13,20 Thereafter, iMCD patients with TAFRO (iMCD-TAFRO) symptoms have been considered to have an aggressive clinical subtype of iMCD. 19 The iMCD patients who do not meet the criteria for TAFRO often have elevated platelet counts, hypergammaglobulinemia, and a less aggressive course; these cases are described as iMCD not otherwise specified (iMCD-NOS).…”
Section: Introductionmentioning
confidence: 99%
“…These features are often used to classify patients into the hyaline vascular/hypervascular, mixed, or plasmacytic histopathological subtypes; limited data exist to indicate clinical relevance of these subtypes. 7 Recently, patients have been divided into clinical subtypes with prognostic implications, including patients with thrombocytopenia, anasarca, fever/elevated C-reactive protein, reticulin myelofibrosis/ renal failure, and organomegaly, referred to as the TAFRO subtype of iMCD (iMCD-TAFRO). [8][9][10][11] Other patients, referred to here as iMCD not otherwise specified (iMCD-NOS) are less well characterized but often demonstrate thrombocytosis, hypergammaglobulinemia, and more mild symptoms.…”
mentioning
confidence: 99%
“…Moreover, it is necessary to rule out POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, skin changes) syndrome, IgG4-related disease, hepatic cirrhosis, thrombotic thrombocytopenic purpura, and hemolytic uremic syndrome before the diagnosis of TAFRO syndrome [ 2 ], which we have conducted and confirmed through the examination results during hospitalization. In addition, autopsy examination of the retroperitoneal lymphadenopathy did not show Castleman's disease-like features such as hyaline vascular, hypervascular, and/or plasmacytic pathology [ 8 ], as described in the diagnostic criteria for TAFRO syndrome [ 2 ]. We speculate that the biopsy results may have been masked by the administration of steroids and immunosuppressive drugs, which interfered with the expression of the typical pathological characteristic of TAFRO syndrome.…”
Section: Discussionmentioning
confidence: 99%